The Substitution Dilemma In Islamic Finance: Contemporary Muslim Legal Thought on the use of Paper Money - Olorogun Lukman Ayinde (Aceh International Journal of Social Science, 2012)
Abstract - Gold and silver became the most widely accepted and circulated form of money in the medieval world. Even though paper money was introduced, state banks continued to store their equivalent in gold. In 1971 the US government abolished the Bretton Woods system and exchanged with the floating or fiat economy system which soon became the standard currency system worldwide. Many economies felt compelled to adopt the new US currency system because of the strength of the all-dominating American dollar and criticism was sparse. Disappointingly, no Muslim government produced legal rulings (fatwas) which rejected the legality of the fiat system and demanded the return to gold and silver backed currency. The single fatwa issued in Saudi Arabia in 1985 concluded that paper currency had completely replaced gold and silver and that all previous Islamic legal rulings issued on gold and silver were now applicable to paper currency. This paper study critically and evaluates the consequences of the Muslim intellectuals and Fiqh Academies‟ approval of substitution of gold and silver by banknotes on the Muslims and their nations.